University social responsibility: The present and future trends based on bibliometric analysis - Muhammad Ashraf, Fauzi; Norwazli, Abdul Wahab; Mohd Hanafiah, Ahmad; Imaduddin, Abidin (Emerald Publishing Limited, 2023)
Purpose – The purpose of this study is to review university social responsibility (USR) using a well-known quantitative approach of bibliometric analysis. Compared to corporate social responsibility (CSR), USR is in its infancy stage, requiring further exploration of its meaning and impact toward higher education institutions (HEIs). Design/methodology/approach – A total of 306 publications and 9,530 cited references were retrieved from the Web of Science database. Bibliographic coupling analysis was applied to uncover present themes, while co-word analysis was used to predict future trends. Findings – Findings suggested that themes are centralized toward the impact of USR on HEIs. USR is important for HEIs to attain excellence in today’s challenging business environment. Research limitations/implications – USR could develop HEIs into world-renowned institutions by establishing a good reputation and engaging with the broader community, locally and internationally. USR is regarded as HEIs’ new value proposition in marketing its brand within the competitive environment in higher education. Originality/value – This study is the first that reviews USR by extracting the knowledge structure and providing visualization on the implicit themes of the subject interest.